2018
DOI: 10.1111/jdv.14957
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence of diabetes mellitus in bullous pemphigoid: it is the dipeptidyl peptidase‐4 inhibitors

Abstract: Linked article: This article is commentary on by L. Fania et al., pp. e439–e440 in this issue. To view this article visit https://doi.org/10.1111/jdv.14965

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
0
14
0
3
Order By: Relevance
“…Furthermore, a recent Greek retrospective cohort study observed a 38.4% increase in the prevalence of patients with comorbid type 2 diabetes mellitus in a cohort of 130 patients with BP. This rise was ascribed mainly to the growing prescription of DPP4i ( 69 ). Interestingly, DPP4i may in addition increase the risk for another pemphigoid disease, namely mucous membrane pemphigoid (MMP), where exposure to these agents accounted for 24 cases of a total of 313 MMP patients in a recent French cohort study ( 70 ).…”
Section: Putative Explanations For This Surgementioning
confidence: 99%
“…Furthermore, a recent Greek retrospective cohort study observed a 38.4% increase in the prevalence of patients with comorbid type 2 diabetes mellitus in a cohort of 130 patients with BP. This rise was ascribed mainly to the growing prescription of DPP4i ( 69 ). Interestingly, DPP4i may in addition increase the risk for another pemphigoid disease, namely mucous membrane pemphigoid (MMP), where exposure to these agents accounted for 24 cases of a total of 313 MMP patients in a recent French cohort study ( 70 ).…”
Section: Putative Explanations For This Surgementioning
confidence: 99%
“…Higher prevalence of BP may be due to the increasing mean age of the population, more frequent use of provoking drugs, such as loop diuretics, penicillin or PD-1/PD-L1 inhibitors, increased incidence of associated diseases (e.g., neurological diseases or hematologic malignancies), and recognition of atypical types of the disease [ 3 , 4 , 5 , 6 , 7 , 8 ]. However, some studies showed a higher prevalence of diabetes mellitus and a higher number of antidiabetic dipeptidyl peptidase 4 inhibitor (DPP4i) taking patients among BP patients [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. An increasing number of studies showed association of DPP4i and bullous pemphigoid, but the exact mechanism of this association remains unclear [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies showed a higher prevalence of diabetes mellitus and a higher number of antidiabetic dipeptidyl peptidase 4 inhibitor (DPP4i) taking patients among BP patients [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. An increasing number of studies showed association of DPP4i and bullous pemphigoid, but the exact mechanism of this association remains unclear [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. As shown by several recent studies, DPP4i-related BP is associated with an atypical form, characterized by erosions without erythema, decreased eosinophil infiltration around the blisters and negative serological results to NC16A domain of BP180 [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that use of DPP-4 inhibitors might be associated with increased risk for developing BP. 24 Sim et al also reported, HT, DM and neurological diseases to be common in patients with BP. 25 Moreover, they emphasized the high incidence of multimorbidity in patients with BP.…”
Section: Discussionmentioning
confidence: 93%